Should We Reject Donated Organs on Moral Grounds or Permit Allocation Using Non‐Medical Criteria?: A Qualitative Study. (1st July 2015) - Moorlock, Greg; Ives, Jonathan; Bramhall, Simon; Draper, Heather
Abstract: Conditional and directed deceased organ donations occur when donors (or often their next of kin) attempt to influence the allocation of their donated organs. This can include asking that the organs are given to or withheld from certain types of people, or that they are given to specified individuals. Donations of these types have raised ethical concerns, and have been prohibited in many countries, including the UK. In this article we report the findings from a qualitative study involving interviews with potential donors (n = 20), potential recipients (n = 9) and transplant staff (n = 11), and use these results as a springboard for further ethical commentary. We argue that although participants favoured unconditional donation, this preference was grounded in a false distinction between 'medical' and 'non‐medical' allocation criteria. Although there are good reasons to maintain organ allocation based primarily upon the existing 'medical' criteria, it may be premature to reject all other potential criteria as being unacceptable. Part of participants' justification for allocating organs using 'medical' criteria was to make the best use of available organs and avoid wasting their potential benefit, but this can also justify accepting conditional donations in some circumstances. We draw a distinction between two types of waste – absolute and relative – and argue that accepting conditional donations may offer a balance between these forms of waste.